A influência da assimetria informacional na estrutura de capital das empresas brasileiras: análise dos segmentos especiais da Bovespa - Tristão, Pâmela Amado (2014)
The study about the way companies structure their policy of financing has been the object of study of several researches, which have originated theories that consider different attributes as determinants of capital structure. However, due to the diversity of factors that can influence the companies decision-making process, none of them could demonstrate precisely the financing mix that companies should use in order to achieve their optimal value. One of these approaches, the Pecking Order theory, which focuses on the informational asymmetry as an important determinant of the capital structure of companies. The aim of this study is to analyze the influence of this informational component in the capital structure of the companies that comprise the special segments of São Paulo Stock Exchage (Bovespa), which were created in 2001 with the aim of distinguishing the companies by the compliance with corporate rules such as the increasing dissemination of information as well as companies that comprise the Traditional Group. To achieve the aim, the methodology of panel data analysis has been used, which has allowed the analysis of the influence of control variables (tangibility, size, profitability, risk and market value) and proxies and dummies related to informational asymmetry in the indebtedness of companies which comprise the special segments: New Market, Levels 2 and 1 of Corporate Governance, and also companies which belong to the Traditional Group. Therefore, the analysis was carried out in two periods: P2, from 2001 to 2013, and P1, from 2007 to 2013. The results demonstrated that in companies, which have adhered the segments of Bovespa, the indebtedness has been used in a lesser extent, furthermore, the proxies related to informational asymmetry have shown negative signals and statistically significance in the segments in which the diffusion of information is more rigid, New Market and Level 2 of Corporate Governance.